2004
DOI: 10.1093/oxfordjournals.schbul.a007145
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Untreated Patients With Schizophrenia: A Meta-Analysis

Abstract: The present meta-analysis investigated the characteristics of sleep in patients with schizophrenia without neuroleptic treatment at the time of sleep recording. The 20 selected studies included 652 participants (321 patients with schizophrenia and 331 healthy subjects). Effect sizes were evaluated using d values for the following sleep variables: sleep latency (SL), total sleep time (TST), sleep efficiency index (SEI), total awake time (TAT), stage 2 percentage (S2%), stage 4 percentage, slow-wave-sleep percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(185 citation statements)
references
References 31 publications
5
175
1
4
Order By: Relevance
“…Clinical observations, subjective reports, and questionnaire studies have been remarkably consistent in showing difficulties falling sleep ("increased sleep latency"), sleep interruptions, and longer need for sleep [4][5][6] in SZ. Indeed, studies suggest that approximately 50% -70% of individuals with SZ experience insomnia [6].…”
Section: Insomnia and Circadian Rhythm Disordersmentioning
confidence: 80%
See 2 more Smart Citations
“…Clinical observations, subjective reports, and questionnaire studies have been remarkably consistent in showing difficulties falling sleep ("increased sleep latency"), sleep interruptions, and longer need for sleep [4][5][6] in SZ. Indeed, studies suggest that approximately 50% -70% of individuals with SZ experience insomnia [6].…”
Section: Insomnia and Circadian Rhythm Disordersmentioning
confidence: 80%
“…Actigraphy monitoring, which allows 24 hr online recording of wrist movements from which sleep is inferred, provides evidence that increased sleep latency and difficulties in maintaining sleep are a characteristic feature of the disorder in medicated and unmedicated individuals e.g. [5,7]. The evidence also suggests that reduced sleep duration is more commonly reported in neuroleptic-naive or drug-free individuals, while a longer need for sleep is reported in medicated samples [4,8], consistent with drug studies demonstrating the sedative properties of antipsychotic medication.…”
Section: Insomnia and Circadian Rhythm Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceci a rapidement donné lieu à un ambitieux projet de recherche sur le sommeil de patients schizophrènes en premier épisode (Chouinard, Poulin, Stip et Godbout, 2004) : dès qu'un patient admissible au projet était inscrit à l'urgence nous étions prévenus et on lui proposait de dormir deux nuits consécutives au laboratoire et de retourner à l'urgence le jour. Une réponse affirmative entraînait une série de démarches dès que le formulaire de consentement était signé : obtenir la confirmation d'Emmanuel Stip qu'il pourrait être présent toute la nuit au laboratoire ou à l'hôpital à titre de médecin de garde pour ce patient, trouver une technicienne de soir pour installer les électrodes sur le patient, trouver un technicien de nuit pour surveiller l'enregistrement et veiller au bien-être du patient.…”
Section: La Petite Histoire : Des Rats Et Des Hommesunclassified
“…Recent studies have indicated a relationship between sleep abnormalities, including alterations in REM/non-REM duration, and some psycho-neurological diseases, such as depression [11,12] and schizophrenia [13,14]. Changes in the REM/non-REM duration in CKD patients have also been described.…”
Section: Introductionmentioning
confidence: 99%